An Act concerning the Kaskaskia Indians, in Nathaniel Pope, Laws of the Territory of Illinois (1815) - (:unkn) unknown (General Publisher, 1815)
Prohibited to trade or gift any horse mare, gun tommahawk, knife, blanket, shrouding, calico, saddle, bridle, or any goods wares or merchandize with the Kaskasia Indians. All such sales and gifts shall be considered fraudulent. Violators fined twenty dollars.
--
Keywords: TRANSFER - DANGEROUS PERSONS